2016
DOI: 10.7897/2230-8407.07653
|View full text |Cite
|
Sign up to set email alerts
|

Basketful Benefit of Citrus Limon

Abstract: Citrus lemon is most important fruit in all over world. Citrus limon is well known nutritional and medicinal property. All part of citrus limon is used as a traditional medicine. Citrus limon belong to the family rutaceae. The main characteristic of lemon plant is thorny branches and white flowers with purple edges. Major medicinal property of Citrus limon include anti-cancer activity, Prevent kidney stones, Bring down a fever, Balance pH. Phytochemically in whole plant contain citral, limonene, terpineol, ger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 2 publications
0
13
0
Order By: Relevance
“…Lemon (Citrus limon) is one of the plants that is very useful for health and comes from Southeast Asia, with its tropical and subtropical climates. 1 One of the places for lemonade plantations in Indonesia is Batu City, East Java Province, located in an active volcanic area, such as Bromo, Tengger, and Semeru, which make land in this area fertile. Batu is located on a plateau, so it has low temperatures and high humidity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lemon (Citrus limon) is one of the plants that is very useful for health and comes from Southeast Asia, with its tropical and subtropical climates. 1 One of the places for lemonade plantations in Indonesia is Batu City, East Java Province, located in an active volcanic area, such as Bromo, Tengger, and Semeru, which make land in this area fertile. Batu is located on a plateau, so it has low temperatures and high humidity.…”
Section: Introductionmentioning
confidence: 99%
“…These EOs contain bioactive compounds, such as limonene, up to 64%-90%, which are believed to have anti-inflammatory activity and low toxicity. 1,5,[7][8][9][10] According to the World Health Organization (WHO), plants are the best source for various types of drugs. The WHO estimates that around 3-4 billion people use herbal medicine and as many as 80% of individuals from developing countries use traditional medicines with basic ingredients from plants.…”
Section: Introductionmentioning
confidence: 99%
“…The results of research conducted by Shrivastava, et al (9) showed that Citrus limon could be used as a pediculicide, and Citrus limon juice without dilution or addition of distilled water could kill 95%5% P. h. capitis within 3 hours. The research results conducted by El Akkad, et al (12) showed that Citrus limon juice had a higher pediculicidal effect (100%) compared to olive oil (96.7%) and tea tree oil (23.3%).…”
Section: Allium Sativum Effectiveness Testmentioning
confidence: 99%
“…C. papaya grown in various parts of the world, including India, tropical America and Europe. 17 Zuhrotun N et al, 18 points out that C. papaya extract have potential as anticancer through mechanism anti-proliferation and apoptosis induction. As Zuhrotun observes: 'mechanism of papaya leaf extract to inhibit the proliferation of breast cancer cells MCF-7 allegedly through the reduction of Reactive Oxygen Species (ROS) by antioxidant compounds contained in papaya leaf extract impact on the decrease of nuclear factor-κB (NF-κB) and impact on the gene expression associated with oxidative stress in MCF-7 cells such as COX-2, AP-1, Bcl-2 and Bcl-XL which can inhibit the proliferation of breast cancer cells MCF-7'.…”
Section: (Product B)mentioning
confidence: 99%